Comparison of common tests performance for Mycobacterium bovis infection diagnosis in low prevalence dairy cattle herds of southern Chile - Raffo, Eduardo; Monti, Gustavo; Salgado, Miguel (Austral Journal of Veterinary Sciences, 2018)
The aim of the present study was to assess the performance of routinely used diagnostic tests to detect M. bovis infection in cattle populations with very low infection prevalence. A cross-sectional study was performed using 609 animals from 17 herds that were sampled for blood interferon, and tested with the caudal fold tuberculin test (CFT). It was planned that animals which showed CFT positive results were sent to the slaughterhouse for post mortem confirmation testing. However, not all the animals considered in the initial sampling were culled. Paired population proportions of positive results for the different diagnostic tools were compared. Apparent sensitivity and specificity was also estimated. Overall, intradermal tuberculin based diagnostics showed better performance in comparison to interferon based test, even though interferon was slightly more specific. From these results, it may be suggested that specific cut-off lines for interferon based techniques for certain areas with particular low bTB prevalence should be considered, as well as the modification of more specific antigens and the use of better combinations of PPDs if in vitro testing is intended must be taken into consideration. The uncertain role of interference bacteria that could be affecting the results of the in vitro analysis must be considered, and perhaps this could explain the apparent lack of consensus of the results obtained in Chile versus the ones obtained elsewhere. More studies must be performed in order to assess this issue.